2023
DOI: 10.1002/jcop.22985
|View full text |Cite
|
Sign up to set email alerts
|

Open pilot trial of an interactive digital application for campus sexual violence prevention

Abstract: Digital applications, or “serious games” for health address learning goals in a cognitively active, interactive manner, with the potential for widespread dissemination. This study used a mixed methods approach to develop and conduct a formative evaluation of a digital application for sexual assault prevention. Make a change is a digital application that uses the principles of games for health to foster learning, engagement, and skill‐building around risk and protective factors for sexual victimization, sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…In a French school of medicine, Lisan et al showed that the implementation of such an 'observatory of mistreatment' may in itself contribute to reducing both sexual harassment and psychological abuse [34] . A formative evaluation of a digital application for sexual assault prevention showed evidence of a trend in reduced frequency of heavy drinking and changes in perceptions of social norms over time [35] .…”
Section: Discussionmentioning
confidence: 99%
“…In a French school of medicine, Lisan et al showed that the implementation of such an 'observatory of mistreatment' may in itself contribute to reducing both sexual harassment and psychological abuse [34] . A formative evaluation of a digital application for sexual assault prevention showed evidence of a trend in reduced frequency of heavy drinking and changes in perceptions of social norms over time [35] .…”
Section: Discussionmentioning
confidence: 99%
“…To help students recognise GBV and learn how to intervene in these situations, more GBV information is needed in prevention education programs that integrates content pertinent to victimisation risk, perpetration risk and bystander intervention skills [ 34 ]. Johnson et al suggested that a semester-long course targeting first-year students could potentially influence knowledge, attitudes and behavioural intentions regarding sexual violence and create a more positive campus climate [ 35 , 36 ]. Additonal programs that depict victims and perpetrators in a gender-neutral manner had more favorable effects on bystander efficacy than programs that depicted victims as all or mostly women or perpetrators as all or mostly men, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 99%